Analisis Hukum Islam Terhadap Penetapan Hakim Yang Menyatakan Tidak Menerima Gugatan Cerai Di Pengadilan Agama Bekasi (Studi Kasus Pada Perkara Nomor : 0234/Pdt.P/2018/PA.Bks) - Angga Isfirnando; Suprihatin - (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
This research aims to answer the question how Islamic law analysis on the determination of thejudge who stated that he did not accept the divorce suit at the bekasi religious court. Even thoughthe religious court may not reject the case filed to find out about this problem, the authors conductedresearch by analyzing the decision namber :0234/Pdt.P/2018/PA.Bks. viewed from the perspectiveof Islamic law. This research is a normative research with descriptive methods, ma gugatan ceraidi Pengadilan Agama Bekasi. namely describing the objeck of research as the actual situation thenanalyzed its suitability with Islamic law. The results of this study state that the judge’s decisionrejecting the divorce suit in case number :0234/Pdt.P/2018/PA.Bks. it is in accordance with Islamiclaw because the judge’s refusal of this lowsuit was because the plaintiff was not present. Therefore, inthe perspective of Islamic law the refusal of the judge is intended to punish the plaintiff and preventthe defendant from slandering the lawsuit.